Community Participation in Recovering Cultural Tourism in Betawi Cultural Village Setu Babakan - Maharani Indira Ravi Mierdhani; Liliana Dewi; Ardi Mularsari (CV ODIS, 2022)
As the cultural centre of the Betawi Tribe, the Betawi Cultural Village is known as a destination that provides cultural tourism to tourists and is one of the destinations that won 1st Place in the 2021 Indonesian Tourism Village Award in the CHSE Category. Behind its success, there is community participation in it. So, this article aims to find out how they form community participation in the recovery of cultural tourism and see its development from the Environmental and Social sides. This article uses a qualitative approach described by descriptive analysis, in-depth interviews, literature studies, and field observations, assisted with the theory of participation and the view of community-based tourism to analyse the forms of community participation and aspects of its development. The results showed that the community participated in the product in Betawi Cultural Village with a record of involvement that is Spontaneous, Coercive and Induced. Based on the aspects of Community-Based Tourism applied in the development process. The UPK and local communities successfully collaborated to realise the values of the environment and socio-culture and use the CHSE protocol to recover cultural tourism. This is also marked by the award of 1st Place in the CHSE Category Tourism Village Award won by the Betawi Cultural Village. This research is reference material and foundation so that the development of Betawi Cultural Village will be better and widely known in the future